Composite protective coating for bolt surface, preparation method and application

By preparing metal nitride/molybdenum disulfide self-lubricating composite coating on the bolt thread surface, the problems caused by bolts due to loosening and wear are solved, achieving higher anti-loosening performance and longer service life.

CN119433448APending Publication Date: 2025-02-14CHINA TOWER CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411648992.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Bolts are easily loose due to plastic deformation and stress relaxation of materials under the action of large preload and alternating loads, and the contact surface of the bearing is severely damaged, resulting in a reduction in the axial force of the bolt, which cannot effectively solve the wear resistance and corrosion resistance of the threaded surface. question.

Method used

Design and prepare metal nitride/molybdenum disulfide self-lubricating composite coating on the bolt thread surface. The friction is reduced through the surface self-lubricating layer, and the bottom metal nitride coating improves wear resistance and load bearing capacity.

Benefits of technology

It significantly improves the anti-loosening performance of bolts, extends its service life, reduces the wear of thread surfaces caused by micro-moving wear and corrosion, and improves the safety and reliability of bolts in tower applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433448A_ABST
    Figure CN119433448A_ABST
Patent Text Reader

Abstract

According to the composite protective coating for the bolt surface, the preparation method and the application, the composite coating takes a bolt of a common model of an iron tower as a substrate, and a cathode arc ion plating technology and a magnetron sputtering technology are combined; the preparation method comprises the four main steps of substrate surface pretreatment, metal bonding layer preparation, metal nitride bearing layer preparation and surface molybdenum disulfide solid self-lubricating layer preparation. According to the method, reliable preparation of the composite coating on the complex thread surface of the bolt is achieved, the anti-loosening capacity of the bolt is remarkably improved through the low friction coefficient, good bearing capacity and excellent wear resistance, and meanwhile the composite coating further has good corrosion resistance and has wide application prospects in iron towers for communication, electric power and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface engineering and relates to a composite protective coating for the surface of a bolt, a preparation method and an application thereof. Background Art

[0002] Bolts are known as the "rice of industry". They are small things with great significance. They are widely used, large-volume and indispensable basic components in towers such as communications and power. Their performance has an important impact on the safety and reliability of the entire tower structure. However, modern industry still has shortcomings in its understanding and control of bolts. The direct economic losses caused by loose bolts and fatigue fractures in countries around the world reach more than billions of dollars each year. Especially in towers in the fields of communications, power, etc., once problems occur due to loose bolts, it will cause serious adverse consequences and far-reaching social impacts.

[0003] The main reason for bolt loosening is that under the dual effects of large preload and alternating load, the axial force of the bolt slowly decreases due to plastic deformation and stress relaxation of the material, and the serious damage to the load-bearing contact surface causes the bolt and nut to rotate relative to each other, causing the axial force of the bolt to decrease rapidly. For tower bolts with certain materials and structures, the micro-wear and corrosion of the load-bearing tooth surfaces in close contact during service are the main factors causing loosening failure. Therefore, optimizing the wear resistance and corrosion resistance of the thread surface and increasing the preload are the keys to preventing bolt loosening. At present, the common anti-loosening method is to adopt bolt anti-loosening structure design, double nut or even multi-nut tightening, etc. On the one hand, this method is costly and the use process is complicated, and on the other hand, it cannot solve the wear and corrosion resistance of the thread surface. Based on this, the present invention proposes to design and prepare a new metal nitride / molybdenum disulfide self-lubricating composite coating on the surface of bolts commonly used in iron towers. The surface self-lubricating layer greatly reduces the friction between the supporting surface and the thread surface, so that the bolts can obtain a higher pre-tightening force under a lower tightening torque, and the bottom strong and wear-resistant layer significantly improves the wear resistance, bearing capacity and friction, effectively preventing the bolts from being damaged or broken due to micro-movement, ensuring good reliability after the bolts are tightened, thereby enhancing the anti-loosening performance of the bolts and realizing long-term safe and reliable service in the iron tower.

[0004] In addition, there are currently no patent reports on the design and preparation of a composite protective coating using a high-hardness, high-load-bearing and high-wear-resistant metal nitride coating as a supporting layer and a solid self-lubricating molybdenum disulfide film as a surface functional layer to improve the anti-loosening performance and application of bolts for towers. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a composite protective coating for the surface of bolts, a preparation method and an application thereof. Aiming at bolts of commonly used specifications for iron towers, the composite protective coating is prepared on the threaded surface of the bolts by combining a metal nitride coating and a molybdenum disulfide-based solid self-lubricating film, which can achieve a good anti-loosening effect.

[0006] The present invention is achieved through the following technical solutions:

[0007] A composite protective coating for the surface of a bolt comprises, from the inside to the outside, a metal bonding layer, a metal nitride bearing layer and a surface solid self-lubricating layer.

[0008] A method for preparing a composite protective coating on a bolt surface comprises the following steps:

[0009] S1. Performing surface etching on the pretreated bolts;

[0010] S2. Using a cathode arc ion plating method, using argon as a working gas, by sputtering a metal target, a metal bonding layer is prepared on the bolt after surface etching;

[0011] S3, based on the metal bonding layer, using nitrogen as a reaction gas, by sputtering a metal target to prepare a metal nitride bearing layer;

[0012] S4. After the metal nitride carrier layer is subjected to surface etching treatment, argon is used as the working gas and a magnetron sputtering method is adopted to sputter a metal target to prepare a bonding layer. After the bias voltage is reduced, a metal target and a molybdenum disulfide target are co-sputtered on the bonding layer to prepare a surface solid self-lubricating layer.

[0013] Preferably, the process of pretreatment of the bolts is:

[0014] The bolt surface was cleaned with rust remover, water-based cleaning agent, petroleum ether and anhydrous ethanol ultrasonically in sequence, and then dried with dry nitrogen;

[0015] The specific process of surface etching is as follows:

[0016] Move the pretreated bolts into the vacuum chamber of the coating preparation system and evacuate until the vacuum degree drops to 5×10 - 3 Pa, 50sccm argon gas was introduced and the bolt surface was etched under the action of the ion source; wherein the bias voltage was set to 200V and the time was set to 40 minutes.

[0017] Preferably, the specific preparation process of the metal bonding layer is:

[0018] The bolts after surface etching are subjected to cathode arc ion plating, 300 sccm of high-purity argon gas is introduced, and the metal target is sputtered to prepare a metal bonding layer;

[0019] The target current in the sputtering metal target is set to 100-150A, the bias voltage is set to 70-100V, and the time is 10 minutes.

[0020] Preferably, the specific preparation process of the metal nitride supporting layer is:

[0021] The metal nitride coating is prepared on the bolts of the metal bonding layer by setting the bias voltage to 50-70V, setting the target current to 100-150A, introducing 800sccm nitrogen, sputtering the metal target material, and the sputtering time is 60-120 minutes.

[0022] Preferably, the specific process of performing surface etching treatment on the metal nitride bearing layer is:

[0023] 16-50 sccm argon gas is introduced and the surface of the metal nitride coating is etched under the action of glow discharge;

[0024] Among them, the bias voltage is set to 500V and the time is set to 30 minutes;

[0025] Preferably, the specific preparation process of the surface solid self-lubricating layer is:

[0026] A magnetron sputtering method is adopted, 16-50sccm argon gas is introduced, the bias voltage is set to 100V, the target current is set to 3-5A, the metal target is sputtered, and a bonding layer is prepared on the metal nitride coating after etching. Then the bias voltage is reduced to 50-70V, and the metal target and molybdenum disulfide target are co-sputtered on the bonding layer to prepare a surface solid self-lubricating layer.

[0027] Preferably,

[0028] The metal target in S2 is a circular single-substance material of Ti or Cr, and the prepared metal bonding layer is a Ti layer or a Cr layer;

[0029] The metal target material in S3 is one of Ti, Cr, TiAl and CrA, and the prepared metal nitride coating is one of TiN, CrN, TiAlN and CrAlN;

[0030] The metal target in S4 is a rectangular Ti or Cr single-substance material, the purity of the molybdenum disulfide target is not less than 99.9%, and the regulated metal content in the surface solid self-lubricating layer is 5-10%;

[0031] A bolt with a composite protective coating on the surface is prepared based on the composite protective coating on the surface of the bolt, or a bolt with a composite protective coating on the surface is prepared based on the preparation method of the composite protective coating on the surface of the bolt.

[0032] The invention discloses an application of a bolt with a composite protective coating on a tower.

[0033] Compared with the prior art, the present invention has the following beneficial technical effects:

[0034] The present invention provides a surface composite protective coating for preventing bolts for iron towers from loosening, which has excellent performance, low cost and good application prospects: the composite protective coating is based on bolts of common specifications of iron towers, and is composed of a strongly bonded metal layer, a tough and wear-resistant metal nitride coating and a solid self-lubricating molybdenum disulfide-based surface layer prepared in sequence on the thread surface by physical vapor deposition technology. The metal nitride coating with high hardness and high wear resistance provides good load-bearing performance during the bolt tightening process, effectively reduces plastic deformation and severe wear on the thread surface, and improves the anti-loosening ability; the molybdenum disulfide functional layer on the surface effectively reduces the friction force during the nut tightening process, which is conducive to improving the pre-tightening force. At the same time, after tightening, the molybdenum disulfide thin layer is destroyed, and the metal nitride layer of the bottom layer plays a load-bearing role. At the same time, because of its high friction coefficient, it maintains the tightening ability of the bolt and improves the anti-loosening performance. The composite protective coating of the present invention has reliable bonding force on the complex thread surface of the bolt; the composite protective coating of the present invention has good corrosion resistance, can effectively improve the corrosion resistance of the bolt surface, and meet the anti-corrosion requirements of the iron tower bolts during service. The present invention adopts arc ion plating technology and unbalanced magnetron sputtering technology to prepare strong and wear-resistant metal nitride coating and solid self-lubricating molybdenum disulfide-based film, and then constructs a composite protective coating, which not only significantly improves the bonding force between the molybdenum disulfide-based film and the substrate, but also enhances the bearing capacity and wear resistance of the composite protective coating. When applied to the complex thread surface of the bolt, it can significantly improve its tribological properties, reduce the loosening phenomenon caused by thread surface wear due to micro-wear and corrosion, effectively improve the anti-loosening performance of the bolt in the tower application, and extend its service life, thereby achieving the purpose of reducing costs and improving safety and reliability.

[0035] Furthermore, by pre-treating the bolt substrate and designing the metal bonding layer, the bonding between the composite coating and the substrate is optimized to ensure that the composite protective coating on the complex thread surface of the bolt has good bonding strength and achieve reliable preparation;

[0036] Furthermore, the high hardness of the metal nitride bearing layer helps to improve the bonding strength by avoiding early plastic deformation of the substrate under loading conditions.

[0037] Furthermore, the metal intermediate layer is generally Cr or Ti, which has good corrosion resistance and can improve the corrosion resistance of the substrate;

[0038] Furthermore, the doped molybdenum disulfide prepared by surface magnetron sputtering has a dense microstructure and good environmental adaptability, which is beneficial to improving the corrosion resistance of the composite coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Flow chart for preparing composite protective coating on the surface of tower bolts;

[0040] Figure 2 is a schematic diagram of the structure of the composite coating;

[0041] In the figure: 1 - bolt matrix; 2 - metal bonding layer; 3 - metal nitride bearing layer; 4 - molybdenum disulfide self-lubricating layer. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0043] The present invention provides a method for preparing a composite protective coating for preventing loosening of bolt surfaces, comprising the following steps:

[0044] (1) Clean the bolt surface with rust remover, water-based cleaning agent, petroleum ether and anhydrous ethanol ultrasonically in sequence, and then blow dry with dry nitrogen for later use;

[0045] (2) Fix the cleaned bolts on a special rotating rack that can achieve self-rotation, and then move them into the vacuum chamber of the coating preparation system to evacuate the vacuum until the vacuum degree drops to 5×10 -3 Pa, 50sccm high-purity argon gas was introduced and the bolt surface was etched under the action of the ion source, with the bias voltage set to 200V and the time set to 40 minutes;

[0046] (3) using a cathode arc ion plating method, introducing 300 sccm of high-purity argon gas, sputtering a metal target to prepare a metal bonding layer, wherein the target current is set at 100 to 150 A, the bias voltage is 70 to 100 V, and the time is 10 minutes;

[0047] (4) Turn off the argon flow meter, set the bias voltage to 50-70 V, sputter the metal target, set the target current to 100-150 A, and introduce 800 sccm of high-purity nitrogen to prepare the metal nitride coating for 60-120 minutes;

[0048] (5) When the chamber temperature drops below 100 degrees Celsius, maintain the vacuum due to 5×10 -3Pa, 16-50sccm high-purity argon gas is introduced and the bolt surface is etched under the action of glow discharge, the bias voltage is set to 500V, and the time is set to 30 minutes;

[0049] (6) A magnetron sputtering method is used, 16 to 50 sccm of high-purity argon gas is introduced, the bias voltage is set to 100 V, the target current is set to 3 to 5 A, and a metal target is sputtered to prepare a bonding layer. The bias voltage is then reduced to 50 to 70 V, and a metal target and a molybdenum disulfide target are co-sputtered on the bonding layer to prepare a surface solid self-lubricating layer.

[0050] The bolts in step (1) are of a commonly used type for iron towers and are made of carbon steel and alloy steel.

[0051] The metal target material in step (3) is a circular single-element material such as Ti and Cr, and the prepared metal bonding layer is a Ti layer and a Cr layer.

[0052] The metal target material of step (4) is a single material or alloy material such as Ti, Cr, TiAl, CrAl, etc., and the prepared metal nitride coating is a binary or ternary coating material such as TiN, CrN, TiAlN, CrAlN, etc.

[0053] The metal target material of step (6) is a rectangular single material such as Ti, Cr, etc., and the purity of the molybdenum disulfide target material is not less than 99.9%. During the co-sputtering process, the metal content is adjusted to 5-10% by setting the current of the molybdenum disulfide target and the metal target differently, the target current of the molybdenum disulfide is set to 0.8-1.2A, and the current of the metal Ti or Cr target is set to 0.2-0.5A.

[0054] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0055] Example 1

[0056] In this embodiment, Figure 1 As shown, a new type of anti-loosening composite protective coating is prepared on the surface of M16 bolts made of carbon steel and with a strength grade of 8.8, which is commonly used in iron towers. The specific steps are as follows:

[0057] (1) Clean the bolt surface with rust remover, water-based cleaning agent, petroleum ether and anhydrous ethanol ultrasonically in sequence, and then blow dry with dry nitrogen for later use;

[0058] (2) Fix the cleaned bolts on a special rotating rack that can achieve self-rotation, and then move them into the vacuum chamber of the coating preparation system to evacuate the vacuum until the vacuum degree drops to 5×10 -3 Pa, 50sccm high-purity argon gas was introduced and the bolt surface was etched under the action of the ion source, with the bias voltage set to 200V and the time set to 40 minutes;

[0059] (3) using a cathode arc ion plating method, introducing 300 sccm of high-purity argon gas, sputtering a metal Cr target to prepare a Cr metal bonding layer, wherein the target current was set to 100 A, the bias voltage was 70 V, and the time was 10 minutes;

[0060] (4) Turn off the argon flow meter, set the bias voltage to 50 V, sputter the metal Cr target, set the target current to 100 A, and introduce 800 sccm of high-purity nitrogen to prepare the chromium nitride coating for 90 minutes;

[0061] (5) When the chamber temperature drops below 100 degrees Celsius, maintain a vacuum better than 5×10 -3 Pa, 20sccm high-purity argon gas was introduced and the bolt surface was etched under the action of glow discharge, with the bias voltage set to 500V and the time set to 30 minutes;

[0062] (6) Using a magnetron sputtering method, 16 sccm of high-purity argon gas was introduced, the bias voltage was set to 100 V, and the metal target was sputtered to prepare a bonding layer. The bias voltage was then reduced to 50 V, and a metal Ti target and a molybdenum disulfide target were co-sputtered to prepare a surface solid self-lubricating layer, such as Figure 2 During the sputtering process, the target current of molybdenum disulfide is set to 0.8A, the target current of metal Ti is set to 0.2A, and the metal content is adjusted to 5% in this embodiment.

[0063] The bolts with the composite coating prepared above were tested as follows:

[0064] (1) Anti-loosening performance test:

[0065] A lateral vibration test was conducted using a vibration testing machine at a fixed torque of 250 Nm, an amplitude of 1 mm, and a frequency of 12.5 Hz. The anti-loosening performance was evaluated based on the number of vibrations obtained when the vibration test was attenuated by 60%. The results are shown in Table 1.

[0066] (2) Salt spray corrosion test

[0067] The salt spray test was carried out using a salt spray test machine with reference to GB10125-1997. The results are shown in Table 1.

[0068] Example 2

[0069] In this embodiment, M16 bolts with carbon steel and strength grade 8.8, which are commonly used in iron towers, are used to prepare a new anti-loosening composite protective coating on their surface. The specific steps are as follows:

[0070] (1) Clean the bolt surface with rust remover, water-based cleaning agent, petroleum ether and anhydrous ethanol ultrasonically in sequence, and then blow dry with dry nitrogen for later use;

[0071] (2) Fix the cleaned bolts on a special rotating rack that can achieve self-rotation, and then move them into the vacuum chamber of the coating preparation system to evacuate the vacuum until the vacuum degree drops to 5×10 -3 Pa, 50sccm high-purity argon gas was introduced and the bolt surface was etched under the action of the ion source, with the bias voltage set to 200V and the time set to 40 minutes;

[0072] (3) using a cathode arc ion plating method, introducing 300 sccm of high-purity argon gas, sputtering a Ti target to prepare a metal Ti bonding layer, wherein the target current was set to 100 A, the bias voltage was 70 V, and the time was 10 minutes;

[0073] (4) Turn off the argon flowmeter, set the bias voltage to 50 V, sputter the CrAl target, set the target current to 130 A, and introduce 800 sccm of high-purity nitrogen to prepare the chromium aluminum nitride coating for 60 minutes;

[0074] (5) When the chamber temperature drops below 100 degrees Celsius, maintain the vacuum due to 5×10 -3 Pa, 20sccm high-purity argon gas was introduced and the bolt surface was etched under the action of glow discharge, with the bias voltage set to 500V and the time set to 30 minutes;

[0075] (6) A magnetron sputtering method was used, 16 sccm of high-purity argon gas was introduced, the bias voltage was set to 100 V, and the metal target was sputtered to prepare a bonding layer. The bias voltage was then reduced to 50 V, and a Cr target and a molybdenum disulfide target were co-sputtered to prepare a surface solid self-lubricating layer. During the sputtering process, the target current of molybdenum disulfide was set to 1.0 A, and the target current of metal Cr was set to 0.4 A. In this embodiment, the metal content was adjusted to 8%.

[0076] The bolts with the composite coating prepared above were tested as follows:

[0077] (1) Anti-loosening performance test:

[0078] A lateral vibration test was conducted using a vibration testing machine at a fixed torque of 250 Nm, an amplitude of 1 mm, and a frequency of 12.5 Hz. The anti-loosening performance was evaluated based on the number of vibrations obtained when the vibration test was attenuated by 60%. The results are shown in Table 1.

[0079] (2) Salt spray corrosion test

[0080] The salt spray test was carried out using a salt spray test machine with reference to GB10125-1997. The results are shown in Table 1.

[0081] Example 3

[0082] In this embodiment, M16 bolts with alloy steel and strength grade 10.9, which are commonly used in iron towers, are used to prepare a new anti-loosening composite protective coating on their surface. The specific steps are as follows:

[0083] (1) Clean the bolt surface with ultrasonic cleaning agent, water-based cleaning agent, petroleum ether and anhydrous ethanol in sequence, and then blow dry with dry nitrogen for later use;

[0084] (2) Fix the cleaned bolts on a special rotating rack that can achieve self-rotation, and then move them into the vacuum chamber of the coating preparation system to evacuate the vacuum until the vacuum degree drops to 5×10 -3 Pa, 50sccm high-purity argon gas was introduced and the bolt surface was etched under the action of the ion source, with the bias voltage set to 200V and the time set to 40 minutes;

[0085] (3) using a cathode arc ion plating method, introducing 300 sccm of high-purity argon gas, sputtering a Ti target to prepare a metal Ti bonding layer, wherein the target current was set to 100 A, the bias voltage was 70 V, and the time was 10 minutes;

[0086] (4) Turn off the argon flowmeter, set the bias voltage to 50 V, sputter the Ti target, set the target current to 150 A, and introduce 800 sccm of high-purity nitrogen to prepare the titanium nitride coating for 60 minutes;

[0087] (5) When the chamber temperature drops below 100 degrees Celsius, maintain a vacuum better than 5×10 -3 Pa, 20sccm high-purity argon gas was introduced and the bolt surface was etched under the action of glow discharge, with the bias voltage set to 500V and the time set to 30 minutes;

[0088] (6) A magnetron sputtering method was used, 16 sccm of high-purity argon gas was introduced, the bias voltage was set to 100 V, and the metal target was sputtered to prepare a bonding layer. The bias voltage was then reduced to 50 V, and the Ti target and the molybdenum disulfide target were co-sputtered to prepare a surface solid self-lubricating layer. During the sputtering process, the target current of the molybdenum disulfide was set to 0.8 A, and the target current of the metal Ti was set to 0.2 A. In this embodiment, the metal content was adjusted to 5%.

[0089] The bolts with the composite coating prepared above were tested as follows:

[0090] (1) Anti-loosening performance test:

[0091] A lateral vibration test was conducted using a vibration testing machine at a fixed torque of 350 Nm, an amplitude of 1 mm, and a frequency of 12.5 Hz. The anti-loosening performance was evaluated using the number of vibrations obtained when the vibration test was attenuated by 60%. The results are shown in Table 1.

[0092] (2) Salt spray corrosion test

[0093] The salt spray test was carried out using a salt spray test machine with reference to GB10125-1997. The results are shown in Table 1.

[0094] In order to further illustrate the advantages of the composite coating of the present invention, the following is used as a comparative example.

[0095] Example 4

[0096] In this embodiment, M16 bolts with alloy steel and strength grade 10.9, which are commonly used in iron towers, are used to prepare a new anti-loosening composite protective coating on their surface. The specific steps are as follows:

[0097] (1) Clean the bolt surface with ultrasonic cleaning agent, water-based cleaning agent, petroleum ether and anhydrous ethanol in sequence, and then blow dry with dry nitrogen for later use;

[0098] (2) Fix the cleaned bolts on a special rotating rack that can achieve self-rotation, and then move them into the vacuum chamber of the coating preparation system to evacuate the vacuum until the vacuum degree drops to 5×10 -3 Pa, 50sccm high-purity argon gas was introduced and the bolt surface was etched under the action of the ion source, with the bias voltage set to 200V and the time set to 40 minutes;

[0099] (3) using a cathode arc ion plating method, introducing 300 sccm of high-purity argon gas, sputtering a Ti target to prepare a metal Ti bonding layer, wherein the target current was set to 150 A, the bias voltage was 100 V, and the time was 10 minutes;

[0100] (4) Turn off the argon flowmeter, set the bias voltage to 70 V, sputter the TiAl target, set the target current to 150 A, and introduce 800 sccm of high-purity nitrogen to prepare the TiAlN coating for 120 minutes;

[0101] (5) When the chamber temperature drops below 100 degrees Celsius, maintain a vacuum better than 5×10 -3 Pa, 50sccm high-purity argon gas was introduced and the bolt surface was etched under the action of glow discharge, with the bias voltage set to 500V and the time set to 30 minutes;

[0102] (6) Using a magnetron sputtering method, 50 sccm of high-purity argon gas was introduced, the bias voltage was set to 100 V, and the metal target was sputtered to prepare a bonding layer. The bias voltage was then reduced to 70 V, and the Ti target and the molybdenum disulfide target were co-sputtered to prepare a surface solid self-lubricating layer. During the sputtering process, the target current of the molybdenum disulfide was set to 0.8 A, and the target current of the metal Ti was set to 0.4 A. In this embodiment, the metal content was adjusted to 8%;

[0103] Example 5

[0104] In this embodiment, M16 bolts with alloy steel and strength grade 10.9, which are commonly used in iron towers, are used to prepare a new anti-loosening composite protective coating on their surface. The specific steps are as follows:

[0105] (1) Clean the bolt surface with ultrasonic cleaning agent, water-based cleaning agent, petroleum ether and anhydrous ethanol in sequence, and then blow dry with dry nitrogen for later use;

[0106] (2) Fix the cleaned bolts on a special rotating rack that can achieve self-rotation, and then move them into the vacuum chamber of the coating preparation system to evacuate the vacuum until the vacuum degree drops to 5×10 -3 Pa, 50sccm high-purity argon gas was introduced and the bolt surface was etched under the action of the ion source, with the bias voltage set to 200V and the time set to 40 minutes;

[0107] (3) using a cathode arc ion plating method, introducing 300 sccm of high-purity argon gas, sputtering a Cr target, and preparing a metal Cr bonding layer, wherein the target current was set to 130 A, the bias voltage was 80 V, and the time was 10 minutes;

[0108] (4) Turn off the argon flowmeter, set the bias voltage to 70 V, sputter the CrAl target, set the target current to 150 A, pass 800 sccm of high-purity nitrogen, and prepare the CrAlN coating for 100 minutes;

[0109] (5) When the chamber temperature drops below 100 degrees Celsius, maintain a vacuum better than 5×10 -3 Pa, 30sccm high-purity argon gas was introduced and the bolt surface was etched under the action of glow discharge, with the bias voltage set to 500V and the time set to 30 minutes;

[0110] (6) A magnetron sputtering method was used, 30 sccm of high-purity argon gas was introduced, the bias voltage was set to 100 V, and the metal target was sputtered to prepare a bonding layer. The bias voltage was then reduced to 60 V, and a Cr target and a molybdenum disulfide target were co-sputtered to prepare a surface solid self-lubricating layer. During the sputtering process, the target current of the molybdenum disulfide was set to 1.0 A, and the target current of the metal Cr was set to 0.4 A. In this embodiment, the metal content was adjusted to 7%.

[0111] Example 6

[0112] In this embodiment, M16 bolts with alloy steel and strength grade 10.9, which are commonly used in iron towers, are used to prepare a new anti-loosening composite protective coating on their surface. The specific steps are as follows:

[0113] (1) Clean the bolt surface with ultrasonic cleaning agent, water-based cleaning agent, petroleum ether and anhydrous ethanol in sequence, and then blow dry with dry nitrogen for later use;

[0114] (2) Fix the cleaned bolts on a special rotating rack that can achieve self-rotation, and then move them into the vacuum chamber of the coating preparation system to evacuate the vacuum until the vacuum degree drops to 5×10 -3 Pa, 50sccm high-purity argon gas was introduced and the bolt surface was etched under the action of the ion source, with the bias voltage set to 200V and the time set to 40 minutes;

[0115] (3) using a cathode arc ion plating method, introducing 300 sccm of high-purity argon gas, sputtering a Cr target, and preparing a metal Cr bonding layer, wherein the target current was set to 130 A, the bias voltage was 80 V, and the time was 10 minutes;

[0116] (4) Turn off the argon flowmeter, set the bias voltage to 70 V, sputter the TiAl target, set the target current to 150 A, introduce 800 sccm of high-purity nitrogen, and prepare the TiAlN coating for 100 minutes;

[0117] (5) When the chamber temperature drops below 100 degrees Celsius, maintain a vacuum better than 5×10 -3 Pa, 30sccm high-purity argon gas was introduced and the bolt surface was etched under the action of glow discharge, with the bias voltage set to 500V and the time set to 30 minutes;

[0118] (6) A magnetron sputtering method was used, 30 sccm of high-purity argon gas was introduced, the bias voltage was set to 100 V, and the metal target was sputtered to prepare a bonding layer. The bias voltage was then reduced to 60 V, and the Ti target and the molybdenum disulfide target were co-sputtered to prepare a surface solid self-lubricating layer. During the sputtering process, the target current of the molybdenum disulfide was set to 1.2 A, and the target current of the metal Ti was set to 0.5 A. In this embodiment, the metal content was adjusted to 10%.

[0119] Comparative Example 1

[0120] The commonly used material in the tower is M16 bolts with carbon steel, strength grade 8.8 and traditional hot-dip galvanized coating.

[0121] Comparative Example 2

[0122] Compared with Example 1, the bolts in this comparative example have the same specifications and materials, there is no surface molybdenum disulfide solid self-lubricating layer in the surface coating, and the rest of the preparation process is the same.

[0123] Comparative Example 3

[0124] Compared with Example 2, the bolts in this comparative example have the same specifications and materials, there is no surface molybdenum disulfide solid self-lubricating layer in the surface coating, and the rest of the preparation process is the same.

[0125] Comparative Example 4

[0126] Compared with Example 3, the bolts in this comparative example have the same specifications and materials, there is no surface molybdenum disulfide solid self-lubricating layer in the surface coating, and the rest of the preparation process is the same.

[0127] Table 1 Comparison of bolt vibration times and salt spray corrosion

[0128]

[0129] From a comprehensive comparison, the composite protective coating used on the surface of the iron tower bolts in the present invention has good performance, its corrosion resistance is comparable to that of the traditional hot-dip galvanized layer, and its anti-loosening performance is much higher than that of the traditional hot-dip galvanized layer, and it has broad prospects in the application of iron towers. The present invention realizes the reliable preparation of the composite coating on the complex thread surface of the bolt, and significantly improves the anti-loosening ability of the bolt through a low friction coefficient, good bearing capacity and excellent wear resistance. At the same time, the composite coating also has good corrosion resistance, and has broad application prospects in iron towers such as communications and power.

[0130] It should be noted that the terms "including" and "having" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or apparatus.

[0131] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0132] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the drawings and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A composite protective coating for bolt surface, characterized in that: The composite protective coating comprises, from the inside to the outside, a metal bonding layer, a metal nitride bearing layer and a surface solid self-lubricating layer.

2. The method for preparing a composite protective coating on a bolt surface according to claim 1, characterized in that: The following steps are involved: S1. Performing surface etching on the pretreated bolts; S2. Using a cathode arc ion plating method, using argon as a working gas, by sputtering a metal target, a metal bonding layer is prepared on the bolt after surface etching; S3, based on the metal bonding layer, using nitrogen as a reaction gas, by sputtering a metal target to prepare a metal nitride bearing layer; S4. After the metal nitride carrier layer is subjected to surface etching treatment, argon is used as the working gas and a magnetron sputtering method is adopted to sputter a metal target to prepare a bonding layer. After the bias voltage is reduced, a metal target and a molybdenum disulfide target are co-sputtered on the bonding layer to prepare a surface solid self-lubricating layer.

3. The method for preparing a composite protective coating on a bolt surface according to claim 2, characterized in that: The process of pretreatment of the bolts is as follows: The bolt surface was cleaned with rust remover, water-based cleaning agent, petroleum ether and anhydrous ethanol ultrasonically in sequence, and then dried with dry nitrogen; The specific process of etching the bolt surface is as follows: Move the pretreated bolts into the vacuum chamber of the coating preparation system and evacuate until the vacuum degree drops to 5×10 -3 Pa, 50sccm argon gas was introduced and the bolt surface was etched under the action of the ion source; wherein the bias voltage was set to 200V and the time was set to 40 minutes.

4. The method for preparing a composite protective coating on a bolt surface according to claim 2, characterized in that: The specific preparation process of the metal bonding layer is as follows: The bolts after surface etching are subjected to cathode arc ion plating, 300 sccm of high-purity argon gas is introduced, and the metal target is sputtered to prepare a metal bonding layer; The target current in the sputtering metal target is set to 100-150A, the bias voltage is set to 70-100V, and the time is 10 minutes.

5. The method for preparing a composite protective coating on a bolt surface according to claim 2, characterized in that: The specific preparation process of the metal nitride bearing layer is as follows: The metal nitride coating is prepared on the bolts for preparing the metal bonding layer by setting the bias voltage to 50-70V, setting the target current to 100-150A, introducing 800sccm nitrogen, sputtering the metal target material, and the sputtering time is 60-120 minutes.

6. The method for preparing a composite protective coating on a bolt surface according to claim 2, characterized in that: The specific process of surface etching the metal nitride bearing layer is as follows: 16-50 sccm argon gas is introduced and the surface of the metal nitride coating is etched under the action of glow discharge; The bias voltage was set to 500 V and the time was set to 30 minutes.

7. The method for preparing a composite protective coating on a bolt surface according to claim 2, characterized in that: The specific preparation process of the surface solid self-lubricating layer is as follows: A magnetron sputtering method is adopted, 16-50sccm argon gas is introduced, the bias voltage is set to 100V, the target current is set to 3-5A, the metal target is sputtered, and a bonding layer is prepared on the metal nitride coating after etching. Then the bias voltage is reduced to 50-70V, and the metal target and molybdenum disulfide target are co-sputtered on the bonding layer to prepare a surface solid self-lubricating layer.

8. The method for preparing a composite protective coating on a bolt surface according to claim 2, characterized in that: The metal target material in S2 is a circular single-substance material of Ti or Cr, and the prepared metal bonding layer is a Ti layer or a Cr layer; The metal target material in S3 is one of Ti, Cr, TiAl and CrAl, and the prepared metal nitride coating is one of TiN, CrN, TiAlN and CrAlN; The metal target material in S4 is a rectangular Ti or Cr single-substance material, the purity of the molybdenum disulfide target material is not less than 99.9%, and the regulated metal content in the surface solid self-lubricating layer is 5-10%.

9. A bolt with a composite protective coating on the surface, wherein the bolt with a composite protective coating on the surface is prepared based on the composite protective coating for the bolt surface according to claim 1, or the bolt with a composite protective coating on the surface is prepared based on the method for preparing the composite protective coating on the bolt surface according to any one of claims 2 to 8.

10. Use of the bolt with a composite surface protective coating as claimed in claim 9 on an iron tower.

Citation Information

Cited By

  • Corrosion-resistant coating for wading fastener and preparation method of corrosion-resistant coating

    CN121183279A

  • High-strength ceramic matrix composite bolt and processing technology

    CN121449431A

  • WS2-based composite coating and preparation method thereof

    CN122105314A